Effect of Deoxyribonucleic Acid Ligands on Deoxyribonucleases and Deoxyribonucleic Acid Polymerase I of Escherichia coli K-12 - Eberhard, Carolyn (1972)
Endonuclease I, exonuclease I, and exonuclease II-deoxyribonucleic acid (DNA) polymerase I activities are not vital functions in Escherichia coli, although the latter two enzymes have been indirectly shown to be involved in DNA repair processes. Acridines such as acridine orange and proflavine interfere with repair in vivo, and we find that such compounds inhibit the in vitro activity of exonuclease I and DNA polymerase I but stimulate endonuclease I activity and hydrolysis of p-nitrophenyl thymidine-5′-phosphate by exonuclease II. Another acridine, 10-methylacridinium chloride, binds strongly to DNA but is relatively inert both in vivo and in vitro. These experiments suggest that acridines affect enzyme activity by interacting with the enzyme directly as well as with DNA. Resulting conformational changes in the DNA-dependent enzymes might explain why similar acridines which form similar DNA complexes have such a wide range of physiological effects. Differential sensitivity of exonuclease I and DNA polymerase I to acridine inhibition relative to other DNA-dependent enzymes may contribute to the acridine sensitivity of DNA repair.